Management of Local Government Website at the Communication and Information Office of East Bolaang Mongondow Regency - Mamonto, Wawan Fermana; Tumber, Goinpeace; Mamonto, Fitri (Technium Social Sciences Journal, 2025)
The purpose of this research is to describe, analyze, and explain the management of local government websites at the Communication and Information Office of East Bolaang Mongondow Regency. This research uses a qualitative descriptive method. The focus of this research is on the Management of Local Government Websites at the Communication and Informatics Office which includes financing, human resource competencies, facilities and infrastructure, and Monitoring and Evaluation. The sub-focus or indicators are budgeting, budget realization, knowledge and skills of website operators, facilities, supervision and leadership involvement. Website Management of the Regional Government of East Bolaang Mongondow Regency has not been implemented properly as evidenced by the many cyber/hacker attacks that occur by Online Gambling Sites. The obstacles faced by the Communication and Informatics Office of East Bolaang Mongondow Regency are inadequate facilities provided, the limited budget ceiling set for the implementation of website management and the lack of operator competence in website security systems. Allocating sufficient funds to the website management activity program and increasing the competence of website operators will make the website management of the East Bolaang Mongondow local government run optimally.